DLP system overview - Yulchiyev Ibrokhimjon Usmonali o’g’li (Zien Journals, 2021)
The DLP system is currently very relevant and is an important tool for the safe implementation of business processes and strategies. Data Leak Prevention systems contain a large number of modules. The modules of almost all systems of this type are the same, except that some modules and their operating principles or the tools they use may differ. In this article, we will take a closer look at this system. That is, we will consider what modules should be in the system and what functions they perform
Keywords: DLP system; business; should; Prevention